Design of a drying system for a rollover carwash machine using CFD. Issue 4 (11th July 2016) - Sabet, Seyyed M.M.; Marques, Jorge; Torres, Rui; Nova, Mario; Nóbrega, João M.
Abstract: This work describes the design and development of a new drying system for a rollover carwash machine with the support of numerical tools. The drying system is composed of a pair of stationary vertical dryers and a moveable horizontal dryer that can adjust itself to the contour of a vehicle. After the definition of the dryers' concept, their performance was assessed individually to check their internal flow pattern and to improve their airflow distribution. These issues are expected to provide feedback on redesign and geometric optimization of the dryers. After redesign of the dryers separately, the behaviour of the complete drying system was studied on actual vehicle models, representative of the shortest and tallest dimensions that can be washed with the existing carwash machine sector. The drying efficiency of the whole system was studied by calculation of shear stress distribution on various surfaces of a given vehicle. The results allowed concluding that the overall drying performance of the design system is very good and assure adequate drying on most vehicles surfaces. The results obtained from numerical studies were then validated with experimental measurements and a good agreement was found between the two. The procedure employed in this work can be applied to support the design and analysis of other mechanical drying systems. Graphical abstract: